Implementation of a Smart Grid Inverter through Embedded Systems - Moreno-Garcia, I. M.; Moreno-Munoz, A.; Domingo-Perez, F.; Pallares-Lopez, V.; Real-Calvo, R.; Santiago-Chiquero, I. (Elektronika ir Elektrotechnika, 2013)
This paper focuses on the integration of the inverter into the Smart Grid environment. This work consists of developing an Intelligent Electronic Device (IED) which can perform measurement and protection functions. This IED becomes part of the inverter electronic equipment as an embedded system. The following work presents the proposed IED architecture for multifunctional processing, synchronization and communication in order to fulfill the requirements of Distributed Generation grid connection. The main parameters measured by the IED are RMS values of voltage and current in the aggregation intervals that indicates the power quality standard and the detection and evaluation of voltage disturbances with higher-order statistics. Different types of disturbances are tested and results obtained are successful. DOI: http://dx.doi.org/10.5755/j01.eee.19.3.1378